Answer:
y = -
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
Explanation:
Given
![(3)/(4y+2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/csn2m6017ld8dpckx5rgstriwryq7eox.png)
The denominator of the expression cannot be zero as this would make it undefined. Equating the denominator to zero and solving gives the value that y cannot be, that is
4y + 2 = 0 ( subtract 2 from both sides )
4y = - 2 ( divide both sides by 4 )
y =
= -
← excluded value